Minocycline-Associated Pseudotumor Cerebri with Severe Papilledema - Simon R. Bababeygy; Michael X. Repka; Prem S. Subramanian (Journal of Ophthalmology)
Background. Pseudotumor cerebri is an acknowledged but unusual complication of oral minocycline use. Vision loss and papilledema have been described as mild and transient, and some authors suggest that treatment is not needed. Methods. Case series of 2 patients with severe papilledema and visual field loss. Results. Severe pseudotumor cerebri developed in 2 nonobese patients taking minocycline. Their disease required further treatment even upon drug discontinuation because of visual field loss and papilledema. Conclusions. Minocycline-associated pseudotumor cerebri is not always a self-limited condition and may require aggressive medical or surgical management.